Mechanical Activation of cPLA2 Impedes Fatty Acid β‐Oxidation in Vein Grafts - Linwei Fan; Yuanjun Tang; Jian Liu; Yueqi Liu; Yiwei Xu; Jiayu Liu; Han Liu; Wei Pang; Yuxuan Guo; Weijuan Yao; Tao Zhang; Qin Peng; et al. (Advanced Science)
Abstract High‐magnitude cyclic stretch from arterial blood pressure significantly contributes to the excessive proliferation and migration of vascular smooth muscle cells (VSMCs), leading to neointima formation in vein grafts. However, the molecular mechanisms remain unclear. This study highlights the critical role of cytosolic Phospholipase A2 (cPLA2)/ Yin Yang 1 (YY1)/ carnitine palmitoyltransferase 1b (CPT1B) signaling in coordinating VSMC mechanical activation by inhibiting fatty acid β‐oxidation. Metabolomic analysis showed that a 15%–1 Hz arterial cyclic stretch, compared to a 5%–1 Hz venous stretch, increased long‐chain fatty acids in VSMCs. cPLA2, identified as a mechanoresponsive molecule, produces excessive arachidonic acid (ArAc) under the 15%–1 Hz stretch, inhibiting CPT1B expression, a key enzyme in fatty acid β‐oxidation. ArAc promotes transcription factor YY1 degradation, downregulating CPT1B. Inadequate fatty acid oxidation caused by knockdown of CPT1B or YY1, or etomoxir treatment, increased nuclear membrane tension, orchestrating the activation of cPLA2. Overexpressing CPT1B or inhibiting cPLA2 reduced VSMC proliferation and migration in vein grafts, decreasing neointimal hyperplasia. This study uncovers a novel mechanism in lipid metabolic reprogramming in vein grafts, suggesting a new therapeutic target for vein graft hyperplasia.